Morpho-Molecular species delimitation within Tonnoira Enderlein (Diptera, Psychodidae): Updates on COI barcode data and the description of five new species - Jaume-Schinkel, Santiago (Zootaxa, 2025)
This work describes five new species of Tonnoira Enderlein, namely, T. acantha sp. nov., T. asymmetrica sp. nov., T. sinuosa sp. nov., T. stria sp. nov., and T. wachi sp. nov., increasing the total number of species in this genus to 33. Additionally, T. conistylus Jaume-Schinkel, 2022 is documented for the first time in Panama. COI barcodes are provided for four of these newly described species and for T. fusiformis Quate & Brown, 2004. Molecular species delimitation analyses demonstrate the effectiveness of COI barcodes in identifying and discovering Psychodidae species in the Neotropics. This work highlights the current state of COI barcoding for Tonnoira species, emphasizing the importance of integrating molecular tools with traditional taxonomy to enhance species identification and conservation strategies. These findings contribute to a more comprehensive understanding of species diversity within this genus and support ongoing biodiversity conservation efforts.